2009
DOI: 10.1002/jca.20218
|View full text |Cite
|
Sign up to set email alerts
|

Low CD34 collection from a healthy blood progenitor cell donor: A case report

Abstract: To our knowledge, no successful engraftment has been reported as yet with such a poor collection of PBPC. The amountof transfused CD34+ cells (0.67 x 10(6)/kg) was significantly less than the minimum required amount (5x 10(6)/kg).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“… 4 6 CD34 is expressed on HSCs and is considered a reliable marker for stem cells with regenerative capacity. 7 Despite the major limitation of lower HSCs, 8 with a single cord blood unit containing approximately 10% fewer stem cells than bone marrow, the number of CD34+ cells obtained per unit volume is similar. 9 Moreover, CD34+ cell count is reported to correlate with the total nucleated cell dose, which is crucial for optimal clinical transplantation outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 6 CD34 is expressed on HSCs and is considered a reliable marker for stem cells with regenerative capacity. 7 Despite the major limitation of lower HSCs, 8 with a single cord blood unit containing approximately 10% fewer stem cells than bone marrow, the number of CD34+ cells obtained per unit volume is similar. 9 Moreover, CD34+ cell count is reported to correlate with the total nucleated cell dose, which is crucial for optimal clinical transplantation outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Moreover, CD34+ cell count is reported to correlate with the total nucleated cell dose, which is crucial for optimal clinical transplantation outcomes. 10 , 11 Although lower doses can also be successful, 8 most studies have reported that the number of viable CD34-positive HSCs is correlated with velocity of engraftment. 9 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal hematopoietic progenitor cell (HPC) collection would consistently contain large doses of CD34+ cells and lymphocytes, but low doses of granulocytes, RBCs, and platelets [1–6]. Even if one were able to collect the optimal HPC product, consistency is difficult to achieve in patients/donors mobilized with growth factors (G‐CSF, GM‐CSF, Plerixafor) [7]. The growth factors promote the release of large quantities of immature granulocytes with specific gravities similar to CD34+ cells.…”
Section: Introductionmentioning
confidence: 99%